2010
DOI: 10.1002/bsl.921
|View full text |Cite
|
Sign up to set email alerts
|

Psychological mechanisms underlying support for juvenile sex offender registry laws: prototypes, moral outrage, and perceived threat

Abstract: In three studies, we investigated support for applying sex offender registry laws to juveniles. Family law attorneys supported registry laws less for juveniles than for adults. Laypeople and prosecutors supported juvenile and adult sex offender registration equally--even though they perceived juveniles as generally less threatening than adults (Study 1)--because most people spontaneously envision a severe sex offender prototype regardless of offender age (Study 2). People are less supportive of registry laws, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
72
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 50 publications
9
72
1
1
Order By: Relevance
“…In another study, Mears et al (2008) found variation in respondent beliefs about prison sentences for sex offenders, with 97% supporting incarceration for sexual assault of a minor, 80% for indecent exposure to a child, and 46% for indecent exposure to an adult. Such findings suggest that, although the public may be fairly unified in its support of punitive measures for certain types of sexual offenders (for example, pedophiles who victimize young children), punitive views may be tempered when respondents are prompted to consider the broader range of behaviors that might be subsumed under the "sexual offender" designation (King & Roberts, 2015;Salerno et al, 2010).…”
Section: Public Support For Sexual Offender Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Mears et al (2008) found variation in respondent beliefs about prison sentences for sex offenders, with 97% supporting incarceration for sexual assault of a minor, 80% for indecent exposure to a child, and 46% for indecent exposure to an adult. Such findings suggest that, although the public may be fairly unified in its support of punitive measures for certain types of sexual offenders (for example, pedophiles who victimize young children), punitive views may be tempered when respondents are prompted to consider the broader range of behaviors that might be subsumed under the "sexual offender" designation (King & Roberts, 2015;Salerno et al, 2010).…”
Section: Public Support For Sexual Offender Policiesmentioning
confidence: 99%
“…This response style is often conceptualized as moral outrage (Bastian, Denson, & Haslam, 2013), with a number of researchers arguing that this response is, in part, responsible for people's negative judgments about sexual offenders (Salerno et al, 2010;Vess, 2009;Willis et al, 2010). These reactions occur non-consciously.…”
Section: 'Feeling First' About Sexual Offendingmentioning
confidence: 99%
“…Craun and Theriot (2009) found that participants reported more concern about a child being sexually abused by an unknown individual (representative of a stranger sexual offender) than an individual known to them. In an undergraduate sample, Harper (2012) found that a juvenile sexual offender (i.e., not representative of the 'dirty old man' view) was judged less punitively than an adult male sexual offender (see also Study 3 in Salerno et al, 2010). …”
mentioning
confidence: 99%
“…For example, several authors have recently examined the notion that people hold a stereotype about who a "sexual offender" might be. Salerno et al (2010) found that judgements about "sexual offenders" (as a homogenised label) were more punitive than judgements made about specific case examples. Similarly, Harris and Socia (2014) reported how the "sexual offender" label elicited more punitive responses to adult and juvenile perpetrators of sexual offences than the more sanitised label of "people who have committed crimes of a sexual nature".…”
Section: Introductionmentioning
confidence: 89%